Synthesis and Quantitative Structure–Activity Relationship of Imidazotetrazine Prodrugs with Activity Independent of O6‑Methylguanine-DNA-methyltransferase, DNA Mismatch Repair, and p53 - Pletsas, Dimitrios; Garelnabi, Elrashied A. E; Li, Li; Phillips, Roger M; Wheelhouse, Richard T (Journal of medicinal chemistry, 2013)
The antitumor prodrug temozolomide is compromised by its dependence for activity on DNA mismatch repair (MMR) and the repair of the chemosensitive DNA lesion, O6-methylguanine (O6-MeG), by O6-methylguanine-DNA-methyltransferase (E.C. 2.1.1.63, MGMT). Tumor response is also dependent on wild-type p53. Novel 3-(2-anilinoethyl)-substituted imidazotetrazines are reported that have activity independent of MGMT, MMR, and p53. This is achieved through a switch of mechanism so that bioactivity derives from imidazotetrazine-generated arylaziridinium ions that principally modify guanine-N7 sites on DNA. Mono- and bifunctional analogues are reported, and a quantitative structure–activity relationship (QSAR) study identified the p-tolyl-substituted bifunctional congener as optimized for potency, MGMT-independence, and MMR-independence. NCI60 data show the tumor cell response is distinct from other imidazotetrazines and DNA-guanine-N7 active agents such as nitrogen mustards and cisplatin. The new imidazotetrazine compounds are promising agents for further development, and their improved in vitro activity validates the principles on which they were designed.